Sistem Informasi Pengolahan Data Karyawan di Perusahaan pada Dinas Tenaga Kerja dan Transmigrasi Kabupaten Ogan Komering Ulu Selata - Sukini Sukini; Abdul Rahman; Pujianto Pujianto (UNIVED Press, 2023)
The Personnel Information System is an integrated system, which includes employee data collection, data processing, procedures, rank, employment status, and computer technology to produce fast, complete and accurate information in order to support personnel administration activities. Personnel storage is the main thing in staffing issues, especially in finding or changing staffing data to then change it according to needs. This Personnel Information System Application was made using descriptive research methods with the type of case study research at the Office of Manpower and Transmigration, Ogan Komering Ulu Setalan Regency , where the data collection techniques used include observation, interviews, and literature studies. For the analysis and design methods used in making the system using the ERD method as a data model and DFD as a process model. Using codeigniter 3 programming and action scripts in making visual code programs. Based on the test results, it was concluded that it allows delays in the data manipulation process and delays in each data display that appears. Meanwhile, based on observations concluded that the system was considered good enough, learnable, easy to use. The system created is in accordance with the needs of the Ogan Komering Ulu Setalan Manpower and Transmigration Office, and this system has been tested using the Black Box testing technique.